Mitochondria-localizing curcumin-cryptolepine Zn(II) complexes and their antitumor activity. (15th January 2021) - Qin, Li-Qin; Liang, Chun-Jie; Zhou, Zhen; Qin, Qi-Pin; Wei, Zu-Zhuang; Tan, Ming-Xiong; Liang, Hong
Graphical abstract: The curcumin-cryptolepine Zn(II) red probe with mitochondria-specific localization and apoptosis-inducing capability have been explored as the theranostic antitumor agents. Highlights: Novel four red Zn(II) complex-based fluorescent probes have been firstly prepared. The probes could synergistically promote mitochondrion-mediated apoptosis. The probes effectively inhibited the growth of T-24 cells in vitro and vivo. Abstract: Many metal complexes are potent candidates as mitochondrial-targeting agents. In this study, four novel Zn(II) complexes, [Zn(BPQA)Cl2 ] (Zn1 ), [Zn(BPQA)(Curc)]Cl (Zn2 ), [Zn(PQA)Cl2 ] (Zn3 ), and [Zn(PQA)(Curc)]Cl (Zn4 ), containing N, N-bis (pyridin-2-ylmethyl)benzofuro[3, 2- b ]quinolin-11-amine (BPQA), N-(pyridin-2-ylmethyl)benzofuro[3, 2- b ]quinolin-11-amine (PQA), and curcumin (H-Curc) were synthesized. An MTT assay showed that Zn1 –Zn4 had strong anticancer activities against SK-OV-3/DDP and T-24 tumor cells with IC50 values of 0.03–6.19 μM. Importantly, Zn1 and Zn2 displayed low toxicities against normal HL-7702 cells. Mechanism experiments demonstrated that probe Zn2 showed appreciable fluorescence in the red region of the spectrum, and substantial accumulation of Zn2 occurred in the mitochondria after treatment, indicating increases in Ca 2+ and reactive oxygen species levels, loss of the mitochondrial membrane potential, and consequent induction of mitochondrial dysfunction at low concentrations. In addition, the probe Zn2 effectively (50.7%) inhibited the growth of T-24 bladder tumor cells in vivo . The probe Zn2 shows potential for use in cancer therapy while retaining the H-Curc as an imaging probe.